2014
DOI: 10.7860/jcdr/2014/8286.4591
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous Actinomycosis: A Case Report

Abstract: Actinomycosis is a subacute or chronic suppurative bacterial infection caused by filamentous gram positive, anaerobic to microaerophilic non acid fast bacilli primarily of the genus Actinomyces that normally colonize the mouth, colon and vagina. Primary cutaneous actinomycosis is a rare entity and is generally associated with trauma. We report a case of primary cutaneous actinomycosis of the back and left axilla in a 32-year-old female patient with no suggestive history of trauma.The diagnosis was suggested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Due to the fact that there was no trauma or bite history in our patient, mode of formation of actinomycosis could not be explained. Bose et al have reported a 32-yearold female patient with a pus-like discharge on the left side of her back and left armpit (14). A similar case has been reported by Roy et al from Delhi, where the 26-year-old patient, who had lesions with purulent discharges in his upper left arm for one year, was diagnosed with actinomycosis and treated with penicillin (15).…”
Section: Discussionmentioning
confidence: 73%
“…Due to the fact that there was no trauma or bite history in our patient, mode of formation of actinomycosis could not be explained. Bose et al have reported a 32-yearold female patient with a pus-like discharge on the left side of her back and left armpit (14). A similar case has been reported by Roy et al from Delhi, where the 26-year-old patient, who had lesions with purulent discharges in his upper left arm for one year, was diagnosed with actinomycosis and treated with penicillin (15).…”
Section: Discussionmentioning
confidence: 73%
“…Minor trauma due to thick grass, thorn prick, or contact with human feces might also be associated [2]. However, several cases show no obvious history of trauma, occupational contact, or any exogenous focus of infection [2, 5, 7]. Our patient also mentioned no history of obvious trauma but, regarding his job as an electrical technician, he could have experienced some unnoticed traumas on his hand to be inoculated with Actinomyces spp.…”
Section: Discussionmentioning
confidence: 92%
“…Literatürde herhangi bir travma olmaksızın derialtı aktinomikoz olguları bildirilmiştir. Bose ve arkadaşları 32 yaşında sırtının sol yanında ve sol koltuk altında püy şeklinde akıntısı olan bir kadın hastayı bildirmiştir (14). Benzer bir olguyu da Roy ve arkadaşları Delhi'den bildirilmiştir; 26 yaşında sol üst kolunda yaklaşık bir yıldır pürülan akıntılı lezyonları olan bir hastaya aktinomikoz tanısı konmuş ve penisilin ile tedavi edilmiştir (15).…”
Section: Olgu Sunumuunclassified